Preparation and characterization of zinc and cobalt (II, III) oxides mixture and direct red 23 diazo dye heterogeneous photocatalysis - Paschoal, Giovanni Bóro; Da Silva, Marcelo Rodrigues; Takashima, Keiko (Springer Nature, 2015)
The decolourization of the direct red 23 diazo dye, commonly used in textile industries, was investigated through the heterogeneous photocatalysis mediated by zinc oxide, n-type semiconductor combined with p-type cobalt oxide at 30°C. The mixture of n- and p-type semiconductors may form a p-n junction, which can decrease the band gap energy and thus increase the photocatalytic activity. This work reports the preparation and characterization of cobalt oxide and oxide mixtures of Zn and Co in 1, 3 and 5% proportions, respectively, as well as their photocatalytic activity, measured by direct red 23 diazo dye decolourization rate constants. These oxides were characterized through the X-ray diffraction, scanning electron microscope, energy-dispersive X-ray spectroscopy, X-ray fluorescence spectroscopy and diffuse reflectance spectrophotometry. The suspension, formed from direct red 23 diazo dye solution and oxide mixtures, was kept in the dark for 1 h at 30°C for diazo dye adsorption on the oxide surface and irradiated by UV light for diazo dye decolourization. The mixture of ZnO containing, respectively, 3 and 5% cobalt oxide showed higher decolourization rate constant in comparison to ZnO.
Keywords: Characterization; Diazo dye; Oxide mixture; P-n junction; Photocatalysis